A π‐Conjugated Chromophore Dye and Its Functional Paper Strips for Visually On‐Site Sensing F− and Its Reaction Mechanism. Issue 14 (10th April 2019) - Hu, Lei; Xu, Jie; Wang, Cong; Zhu, Yanjie; Tang, Yulian; Yin, Liwen; Yan, Zhengquan
Abstract: An improved D−A‐D typed π‐conjugated optical chromophore (PBHPI) with multi‐activated recognition sites and its functionalized testing‐paper strips were constructed and developed, for the first time, based on B3LYP/6‐31G level of theory in Gaussian 03 suite. After its UV‐vis spectral property was investigated in detail, it was noted to find that the target PBHPI and its functionalized paper strips could conclusively react with F − with obvious color change from light yellow to dark red. Under the optimized experimental conditions, both PBHPI and its functionalized paper‐strips could selectively recognize F − with a double‐wavelength colorimetric response to realize a wide linear range from 5.0 ×10 –6 mol/L to 1.4 ×10 –4 mol/L. The present sensing systems were successfully applied for visually on‐site monitoring F − in some commercial organic and toothpaste samples simply and conveniently. The recognition mechanism was confirmed to be the deprotonating mechanism to form multiple hydrogen bonds as what we expected. Abstract : An improved D−A‐D π‐conjugated optical chromophore (PBHPI) with multi‐activated recognition sites and its functionalized testing‐paper strips were constructed and developed, for the first time, for conveniently and inexpensively on‐site monitoring F− in some commercial organic and toothpaste samples with excellent selectivity and sensitivity by deprotonating mechanism to form multiple hydrogen bonds.